Sparring And Neurological Function In Professional Boxers - John W Stiller; John W Stiller; John W Stiller; John W Stiller; Steven eYu; Lisa Anne Brenner; Lisa Anne Brenner; Patricia eLangenberg; Phillip eScrofani; Phillip eScrofani; Patrick ePannella; Edbert eHsu; et al. (Frontiers Media S.A., 2014)
AbstractDespite increased interest regarding the potentially long-term negative impact of chronic traumatic brain injury (CTBI), limited research had been conducted regarding such injuries and neurological outcomes in real world settings. To increase understanding regarding the relationship between sparring (e.g., number of years actively training for professional boxing) and neurological functioning, professional boxers (n = 237) who competed in Maryland between 2003 to 2008 completed measures regarding sparring exposure (Cumulative Sparring Index; CSI) and performance on tests of cognition (Symbol Digit Modalities Test; SDMT) and balance (Sharpened Romberg Test; SRT). Measures were completed prior to boxing matches. Higher scores on the CSI (increased sparring exposure) were associated with poorer performance on both tests of cognition (SDMT) and balance (SRT). A threshold effect was noted regarding performance on the SDMT, with those reporting CSI values greater than about 150 experiencing a decline in cognition. A history of frequent and/or intense sparring may pose a significant risk for developing boxing associated neurological sequelae. Implementing administration of clinically meaningful tests before bouts, such as the CSI, SDMT, and/or the SRT, as well as documentation of results into the boxer's physicals or medical profiles may be an important step for improving boxing safety.